2019
DOI: 10.3352/jeehp.2019.16.17
|View full text |Cite
|
Sign up to set email alerts
|

Development of a self-assessment tool for resident doctors’ communication skills in India

Abstract: Purpose: Effective communication skills are essential for resident doctors to provide optimum patient care. This study was conducted to develop and validate a questionnaire for the self-assessment of resident doctors’ communication skills in India.Methods: This was a mixed-methods study conducted in 2 phases. The first phase consisted of questionnaire development, including the identification of relevant literature, focus group discussions with residents and experts from clinical specialties, and pre-testing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…The age and gender demographics of participants are in concordance with studies conducted elsewhere in India. 9 In our study the participating residents did their undergraduate training in various teaching hospitals of North India and many claimed to have prior knowledge of the word ADR. Similarly, various studies have reported high awareness of the term ADR and pharmacovigilance.…”
Section: Discussionmentioning
confidence: 99%
“…The age and gender demographics of participants are in concordance with studies conducted elsewhere in India. 9 In our study the participating residents did their undergraduate training in various teaching hospitals of North India and many claimed to have prior knowledge of the word ADR. Similarly, various studies have reported high awareness of the term ADR and pharmacovigilance.…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire was developed and validated using a standard scientific approach [11][12][13]. This included a thorough study of the literature, in-depth interviews, focus group discussions, expert opinions, pilot testing, and validation.…”
Section: Methodsmentioning
confidence: 99%
“…The development and validation of the questionnaire were performed using a mixed-method design with standardized techniques (Figure 1 ) [ 13 , 14 , 15 ]. The study was approved by the Institute Ethics Committee of the All India Institute of Medical Sciences, New Delhi (IEC-844/06.12.2019, RP-46/2020).…”
Section: Methodsmentioning
confidence: 99%